Cerebral edema induced by laser interstitial thermal therapy and radiotherapy in close succession in patients with brain tumor. Issue 9 (25th May 2018) - Maraka, Stefania; Asmaro, Karam; Walbert, Tobias; Lee, Ian
Abstract : Objective: Laser interstitial thermal therapy (LITT) is an image‐guided technique that uses high temperature to ablate pathological tissue. Brain tumor patients undergoing LITT may also undergo radiation therapy (RT) either before or after LITT. Both procedures have been reported to increase cerebral edema and thereby the two treatments in close succession may worsen existing edema that can be difficult to control. The purpose of our study was to determine the frequency of increased and/or symptomatic cerebral edema after combined LITT and RT, the radiographic and clinical signs of this cerebral edema, and the treatment required. Materials and Methods: This is a single center, retrospective study of patients who underwent LITT and RT less than 60 days apart. Brain Magnetic Resonance Imaging (MRI) and clinical information were reviewed at three time points (pre‐treatment, post‐LITT, and post‐RT). Results: The study cohort comprised eight patients: six with glioblastoma, one with anaplastic astrocytoma, and one with metastasis. Pre‐treatment MRI showed cerebral edema in seven patients. Post‐LITT MRI showed worsening cerebral edema in three patients, of which one was symptomatic. Post‐RT MRI showed worsening cerebral edema in one patient. One patient who received RT before LITT had asymptomatic cerebral edema post‐RT that improved post‐LITT. Three patients required prolonged steroid therapy (>65 days), while two patients required bevacizumab for steroid‐refractory edema. Conclusions: LITT and RT treatment in close succession can induce cerebral edema, which can usually be managed successfully with steroids, although the treatment period may be prolonged. A minority of patients may require more aggressive treatment, such as bevacizumab. Lasers Surg. Med. 50:917–923, 2018. © 2018 Wiley Periodicals, Inc.